Proposed Negative Statutory Instruments under the European Union (Withdrawal) Act 2018 : Criminal Legal Aid (Remuneration) (Amendment) (No. 2) Regulations 2018 : 11th Report of Session 2017-19 /: Criminal Legal Aid (Remuneration) (Amendment) (No. 2) Regulations 2018 : 11th Report of Session 2017-19. ([2019-01-10]) - Unknown
No abstract available